The effect of diabetes exercise on the quality of life of type 2 diabetes mellitus patients - Nur Rachmawati Maulida; Jongky Hendro Prajitno; Nuniek Nugraheny Sulistiawaty (Jurnal Keolahragaan, 2022)
Physical inactivity and obesity are some of the main risk factors for diabetes mellitus (DM). The presence of DM might result in impaired quality of life (QoL). Our study aimed to firstly determine the association between diabetes exercise status and the QoL in type 2 Diabetes Mellitus (T2DM) patients and secondly to explore other factors associated with QoL among T2DM patients. This was an observational study with cross-sectional design of T2DM patients in dr. Trimurti primary health care (PHC) from January – December 2019. The subjects were recruited consecutively then categorized into treatment group (who performed diabetes exercise program) and control group (who did not perform diabetes exercise program).  then observed as in the exercise group (who performed diabetes exercise program) and in the non-exercise group (who did not perform diabetes exercise program). The dependent variable was the QoL and was collected through a modified questionnaire made from 30 questions. The maximum score for QoL was 120 (all 4 on the Likert scale) and the score results were categorized as poor if the score was 96.5 and good if the score was 96.5. Meanwhile, other data (comorbidities, exercise status, glycaemic status) were obtained through medical records. A total of 60 adult T2DM patients were recruited, consisting of 30 subjects each in the non-exercise and exercise groups. Male subjects, aged 65 years, had bachelor's degrees, retired, married, had very high income, had no comorbidities, and exercised independently every week tended to have good QoL. In the exercise group, the majority of subjects (60%) performed diabetes exercise every two weeks and the majority (90%) had random blood glucose levels 200 mg/dL. The chi-square test revealed a significant associaton between participation in diabetes exercise and QoL in T2DM subjects. Participation in diabetes exercise is associated with good QoL and better glycemic control in T2DM patients.